2002
DOI: 10.1042/0264-6021:3630157
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor corepressor-dependent repression of peroxisome-proliferator-activated receptor δ-mediated transactivation

Abstract: The nuclear receptor corepressor (NCoR) was isolated as a peroxisome-proliferator-activated receptor (PPAR) delta interacting protein using the yeast two-hybrid system. NCoR interacted strongly with the ligand-binding domain of PPAR delta, whereas interactions with the ligand-binding domains of PPAR gamma and PPAR alpha were significantly weaker. PPAR-NCoR interactions were antagonized by ligands in the two-hybrid system, but were ligand-insensitive in in vitro pull-down assays. Interaction between PPAR delta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 52 publications
1
65
1
1
Order By: Relevance
“…In the absence of ligand, co-repressor proteins, such as nuclear co-repressor (NCoR), link DNA-bound nuclear receptors to enzymes with histone deacetylase activity that cause chromatin condensation (15). Binding of a ligand with agonistic properties to the nuclear receptors causes a conformational change within their ligand-binding domain that results in the replacement of co-repressors by co-activator proteins, such as receptor-associated co-activator 3 (16) or PPAR␥ co-activator 1␣ (PGC-1␣) (17).…”
mentioning
confidence: 99%
“…In the absence of ligand, co-repressor proteins, such as nuclear co-repressor (NCoR), link DNA-bound nuclear receptors to enzymes with histone deacetylase activity that cause chromatin condensation (15). Binding of a ligand with agonistic properties to the nuclear receptors causes a conformational change within their ligand-binding domain that results in the replacement of co-repressors by co-activator proteins, such as receptor-associated co-activator 3 (16) or PPAR␥ co-activator 1␣ (PGC-1␣) (17).…”
mentioning
confidence: 99%
“…PPARA has high homology (w71%) in the amino acid sequence of its LBD with the PPARG-LBD (Xu et al 2002, Agostini et al 2004. Direct binding of CoRs with wild-type PPARG2 was demonstrated by GST pulldown assay (Zamir et al 1997, Krogsdam et al 2002, Stanley et al 2003, co-immunoprecipitation (Gurnell et al 2000, Yu et al 2005, gel shift assay (Lee et al 2002), and an in vitro pulldown assay with RXR-PPARG2 heterodimers on PPREs (Krogsdam et al 2002). Using a ChIP assay, Guan et al (2005) showed that, in adipocytes without the addition of an exogenous ligand, PPARG2 molecules associated with CoRs are present in PPREs in the promoter region of the glycerol kinase gene .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of CoRs with unliganded PPARG2-LBD has been demonstrated in vitro (Zamir et al 1997, Krogsdam et al 2002, Lee et al 2002, Stanley et al 2003 and in vivo (Gurnell et al 2000, Wang et al 2004, Yu et al 2005. RNA interference assays against the CoR genes , Yu et al 2005 and chromatin immunoprecipitation assays (ChIP) suggest that PPARG2 associates with CoR in vivo and suppresses the basal transcriptional activity of PPARG2-target genes including glycerol kinase , oxidized low-density lipoprotein receptor 1 , aP2, and PPARG itself (Picard et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests co-repressors as general antagonists of the various stimuli inducing PPAR-mediated transactivation. Co-repressors can display different ligand selectivity: the nuclear receptor co-repressor NCoR interacted strongly with the ligand-binding domain of PPAR / , whereas interactions with the ligand-binding domains of PPAR and PPAR were significantly weaker (Krogsdam, Nielsen et al 2002). Very recently, a team of Harvard Medical School researchers has shown that PPAR is phosphorylated at Ser273 by cyclin dependent kinase 5 (CDK5) during obesity which results in deregulation of a subset of genes; including a number of key metabolic regulators, such as adipsin, the first fat cell-selective gene whose expression is altered in obesity and adiponectin, a central regulator of insulin sensitivity in vivo (Choi, Banks et al).…”
Section: Mechanism Of Ligand-independent Transrepressionmentioning
confidence: 99%